Amygdala volume in a population with special educational needs at high risk of schizophrenia - Welch, K. A.; Stanfield, A. C.; Moorhead, T. W.; Haga, K.; Owens, D. C. G.; Lawrie, S. M.; Johnstone, E. C. (Psychological medicine, 2010)
The mildly learning disabled population has a three-fold elevated risk for schizophrenia. It has been proposed that in some individuals this cognitive limitation is a pre-psychotic manifestation of early onset schizophrenia. We examined clinical and neuroanatomical measures of a putative extended phenotype of schizophrenia in an adolescent population receiving special educational assistance. We predicted that people with intellectual impairment and schizotypal features would exhibit amygdala volume reduction as one of the neuroanatomical abnormalities associated with schizophrenia. Assessment by clinical interview, neuropsychological assessment and magnetic resonance imaging scanning was carried out in 28 intellectually impaired individuals identified as being at elevated risk of schizophrenia due to the presence of schizotypal traits, 39 intellectually impaired controls and 29 non-intellectually impaired controls. Amygdala volume was compared in these three groups and the relationship between symptomatology and amygdala volume investigated. Right amygdala volume was significantly increased in the elevated risk group compared with the intellectually impaired controls (p=0.05). A significant negative correlation was seen between left amygdala volume and severity of negative symptoms within this group (p<0.05), but not in either control group. Intellectually impaired subjects judged to be at elevated risk of schizophrenia on the basis of clinical assessment exhibit structural imaging findings which distinguish them from the generality of learning disabled subjects. Within this population reduced amygdala volume may be associated with negative-type symptoms and be part of an extended phenotype that reflects particularly elevated risk and/or early manifestations of the development of psychosis.